Molecular detection, serotyping and phylogenetic analysis of Haemophilus parasuis in Peninsular Malaysia - Lee, Chee Yien (2019)
Haemophilus parasuis infections, what is known to cause Glässer’s disease has been a nuisance for all farms. The lack on the information of H. parasuis serotype complicates vaccination as current available commercial vaccines are serotype-based and efficacy is serotype-dependent. Hence, this study carried the objectives to detect H. parasuis in clinical samples from weaner pigs in Peninsular Malaysia with conventional polymerase chain reaction (PCR) assay; to detect H. parasuis serotype 4, 5 or 12 and 13 using multiplex PCR as these serotypes were prevalent in other countries; to detect the outer membrane protein P2 (OMPP2) gene and further investigate the phylogenetic relatedness of Peninsular Malaysia’s H. parasuis with reference strains. Throughout October 2016 to June 2018, samples were collected from nine farms from northern, seven farms from central and four farms from southern regions of Peninsular Malaysia using convenience sampling method. A total of 87 pigs was sampled and from there, 323 samples were collected. The number of pigs and samples collected in each farm varied depending case availability and gross post mortem manifestation. Samples collected included lung, brain, bodily fluids and fibrins of various sites. Samples were screened for H. parasuis using conventional PCR assay and positive samples were serotyped by multiplex PCR. Finally, representative samples of every states and serotypes were subjected to conventional PCR assay for OMPP2 gene detection; followed by sequencing and phylogenetic analysis on sequences obtained. Using conventional PCR assay, 58/87 (66.7%) of the pigs sampled were positive of H. parasuis. The region with highest detection of H. parasuis in pigs was the southern region (4/5), followed by northern region (12/18) and central region (42/64). Pigs apparent of H. parasuis infection (Category A, B and C) had a higher detection percentage compared to those that were unapparent (Category D, E and F). Among all of the sample types collected, the highest detection percentage was obtained in the pleural fibrin samples (85.7%).Generally, multiplex PCR assay on H. parasuis–positive samples revealed that serotype 4, 5 or 12 and 13 were detected with predominance order of NT, 5 or 12 and followed equally by serotype 4 and 13. Furthermore, comparison of the partial H. parasuis OMPP2 nucleotide sequence of 15 Malaysian isolates and 16 reference strains showed Malaysia isolates were closely related to China strains. There was no direct correlation between serotype and OMPP2 gene. Moreover, phylogenetic analysis of OMPP2 gene revealed that majority of Peninsular Malaysia isolates was found to belong to H. parasuis genetic type III group. In conclusion, H. parasuis and the three important serotypes 4, 5 or 12 and 13 were detected using PCR technique. The phylogenetic relatedness based on the OMPP2 gene and its correlation with serotype was identified. The OMPP2 gene served to be an important virulence gene and future studies should focus on this gene. Equip with the knowledge of this study, more effective control measures could be designed and implemented to control H. parasuis infections in Peninsular Malaysia.